Fabrication of calcium alginate/gum arabic/egg shell composite microbeads for adsorptive removal of methylene blue dye from aqueous solutions - Sandikci, Melike Nisa; Isik, Birol (POLYMER SOC KOREA, 2025)
This study focuses on the design and application of calcium alginate/gum arabic/eggshell powder composite microbeads (CA/GA/ES10) for the removal of methylene blue dye from aqueous solutions through the adsorption method. The characterization of adsorbents was conducted utilizing ATR-FTIR, SEM, XRD, TGA, and pHpzc. The pHpzc value of CA/GA/ES10 composite microbeads was determined as 5.56. From optimization studies, the contact time, adsorbent dosage, and pH values were determined as 60 min, 0.1 g/50 mL, and congruent to 7, respectively. The adsorption raw data have been utilized in the non-linear Langmuir, Freundlich, Temkin, and Sips models. The maximum adsorption capacity of CA/GA/ES10 composite microbeads, as per the Sips, was determined to be 33.30 mg/g at 298 K. The high correlation coefficients (r2\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$r {2}$$\end{document} = 0.9976) and low error functions (chi 2\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\chi {2}$$\end{document} = 0.03) indicate that the non-linear Langmuir is the most appropriate isotherm for the adsorption process. From the Langmuir model, the maximum adsorption capacity was determined as 29.71 mg/g at 298 K. The adsorption process adheres to a non-linear pseudo-second-order (r2\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$r {2}$$\end{document} = 0.9999) and Elovich (r2\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$r {2}$$\end{document} = 0.9999) models. According to thermodynamic results, the adsorption process occurs exothermic (Delta H degrees=-3.77kJ/mol\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\Delta H { \circ } = - 3.77\;{\text{kJ/mol}}$$\end{document}) and spontaneous (Delta G degrees=-25.83kJ/molat298K\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\Delta G { \circ } = - 25.83\;{\text{kJ/mol}}\;{\text{at}}\;298\;{\text{K}}$$\end{document}) in nature. The impact of varying salt concentrations on the adsorption process was assessed. According to the salt effect, the removal percentage decreased from 81.12 to 65.15% with the addition of NaCl, and from 81.12 to 58.78% with the addition of CaCl2. The reusability tests show that the composite microbeads created can be used repeatedly for up to 7 cycles. After the 7th cycle, the removal of MB dye decreased from 81.11 to 53.45%. All results showed that the prepared ternary composite microbeads are effective adsorbents for the removal of cationic dye from aqueous solutions.
Keywords: Adsorption; Calcium alginate; Eggshell; Gum arabic; Methylene blue; Reusability; ENHANCED ADSORPTION; SODIUM ALGINATE; GRAPHENE OXIDE; IONIC-STRENGTH; GUAR GUM; ADSORBENT; ISOTHERM; NANOCOMPOSITE; KINETICS; SORPTION; Polymer Science